VERSE-guided numerical RF pulse design: A fast method for peak RF power control - Lee, Daeho; Grissom, William A.; Lustig, Michael; Kerr, Adam B.; Stang, Pascal P.; Pauly, John M. (Magnetic resonance in medicine, 2012)
In parallel excitation, the computational speed of numerical radiofrequency (RF) pulse design methods is critical when subject dependencies and system nonidealities need to be incorporated on‐the‐fly. One important concern with optimization‐based methods is high peak RF power exceeding hardware or safety limits. Hence, online controllability of the peak RF power is essential. Variable‐rate selective excitation pulse reshaping is ideally suited to this problem due to its simplicity and low computational cost. In this work, we first improve the fidelity of variable‐rate selective excitation implementation for discrete‐time waveforms through waveform oversampling such that variable‐rate selective excitation can be robustly applied to numerically designed RF pulses. Then, a variable‐rate selective excitation‐guided numerical RF pulse design is suggested as an online RF pulse design framework, aiming to simultaneously control peak RF power and compensate for off‐resonance. Magn Reson Med 67:353–362, 2012. © 2011 Wiley Periodicals, Inc.